2005
DOI: 10.1097/00075197-200501000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Unique characteristics of the geriatric diabetic population and the role for therapeutic strategies that enhance glucagon-like peptide-1 activity

Abstract: Elderly diabetics are a growing subset of the type 2 diabetic population with unique pathophysiologic characteristics and diabetic risk profiles. Therapeutic strategies that incorporate enhancement of GLP-1 action on beta-cells to improve beta-cell insulin secretion and glycemic control may be ideal for this distinct population and should be validated with further long-term clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In both treatment groups, treatment efficacy was sustained for longer in older than in younger patients; sustainability was also greater with vildagliptin than glimepiride (361 vs. 309 days for patients ≥65 years). This could be linked to the fact that T2DM in elderly patients may have a different disease pathology to that in younger patients, with a greater contribution of postprandial glycaemia to overall glucose control, and greater hyperglucagonaemia [27–29]. We have shown that vildagliptin, but not glimepiride, therapy results in improved postprandial α ‐cell function that persists for at least 2 years [18].…”
Section: Discussionmentioning
confidence: 87%
“…In both treatment groups, treatment efficacy was sustained for longer in older than in younger patients; sustainability was also greater with vildagliptin than glimepiride (361 vs. 309 days for patients ≥65 years). This could be linked to the fact that T2DM in elderly patients may have a different disease pathology to that in younger patients, with a greater contribution of postprandial glycaemia to overall glucose control, and greater hyperglucagonaemia [27–29]. We have shown that vildagliptin, but not glimepiride, therapy results in improved postprandial α ‐cell function that persists for at least 2 years [18].…”
Section: Discussionmentioning
confidence: 87%
“…According to the Korean National Health and Nutrition Examination Survey (16), 45% of Koreans 65 yr and older meet the diagnostic criteria for type 2 diabetes or impaired glucose tolerance. With aging, beta-cell function declines, and basal insulin secretion level decreases (17). In addition, the interaction of many factors associated with aging likely contributes to the altered glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that GLP-1 mobilizes the intracellular Ca 2+ stores by triggering partial activation of the L-type Ca 2+ channel. The RyR is a Ca 2+ channel composed of four ~550 kDa ryanodine protomers and four 12 kDa FK506 binding proteins that are the regulatory units FKBP12 or FKB12.6 (Thearle and Brillantes, 2005). There are three distinct genes encoding three ryanodine receptors, types 1, 2, and 3, RyR1, RyR2 and RyR3 respectively and there is some debate over the most prevalent and the most important types in the β cell (reviewed in Bruton et al, 2003).…”
Section: Elevation Of [Ca 2+ ] Imentioning
confidence: 99%